G181(P) Long term parental supplementation of vitamin A in preterm neonates: Is it time for a change?. (24th May 2017) - Ord, H; Harper, C; Pearson, F; Marino, L; Saha, A; Batra, A
Abstract : Background: Vitamin A is known to be an important micronutrient for immune competence, retinal cell and lung development. Preterm infants are recognised as having reduced Vitamin A stores and therefore being at greater risk of deficiency and its consequences. Aims: To assess adequacy of vitamin A supplementation via parenteral nutrition (PN) for preterm infants. Methods: A retrospective audit of all pre term infants children receiving PN for greater than 28 days, between January 2009 and December 2013 was performed. Serum concentration of vitamin A at weeks 4–6 and at 90 days were recorded. Vitamin A deficiency was defined as serum concentration below 200 mg/L (0.7 mmol/L) and severe deficiency was defined as below 100 mg/ L (0.35 mmol/L). Results: Vitamin A deficiency was seen in 74% n=32 infants. Infants with low vitamin A had a median gestation age of 26 weeks whereas with normal Vitamin A levels were 30.5 weeks. Most infants (n=27, 84.4%)£1500 gms were deficient in Vitamin A and of these more than half (n=15) had severe deficiency. In comparison to these, infants with birth weight >1500 gms had low vitamin A levels in 5 cases (45%) and none had severe deficiency. Conclusion: This study has added further weight to evidence that preterm infants at the extreme ends of prematurity are at greatest risk of Vitamin A deficiency, despite adequate parenteral supplementation. It suggests the current recommended vitamin A dose, is inadequate and should be supplemented with oral or intramuscular Vitamin A.